ChemInform Abstract: Syntheses, Structures and Optoelectronic Properties of Spiroconjugated Cyclic Ketones. Issue 39 (8th September 2016) - Wilbuer, Jennifer; Schnakenburg, Gregor; Esser, Birgit
Abstract: A short two‐step protocol is developed for the synthesis of spiro‐tetraketone (IV).